Investigating daylight performance of classrooms at a higher educational institution / Wan Nur Hanani Wan Abdullah, Asniza Hamimi Abdul Tharim and Asmat Ismail - Wan Abdullah, Wan Nur Hanani; Abdul Tharim, Asniza Hamimi; Ismail, Asmat (2021)
Daylight is a significant element in the design of educational institutions, as it provides a friendly environment, encourages healthier conditions and guarantees energy savings. This study focuses on investigating the illuminance level of three (3) existing selected case study classrooms at a higher education institution. Hence, a field measurement for indoor and outdoor daylight level was carried out for five (5) days at all of the selected classrooms. Measurement data were recorded and analyzed using Excel graphs. The findings indicate that the daylight performance for all the case study classrooms was below and above the recommended range as set out in the MS1525:2019. The overall findings of this study reveal that classroom design is inadequate to handle daylight in classrooms. The probable explanation for the unacceptable illuminance level results is that the different design of the classroom influences the amount of illumination and the performance of daylight in the classroom. This study has led to the identification of issues that affect low daylight performance in higher educational institutions and should be seen as a reference to promote greater awareness of the advantages of daylight for occupants.